Physical restraining of nursing home residents in the last week of life: An epidemiological study in six European countries. (April 2020) - Pivodic, Lara; Smets, Tinne; Gambassi, Giovanni; Kylänen, Marika; Pasman, H. Roeline; Payne, Sheila; Szczerbińska, Katarzyna; Deliens, Luc; Van den Block, Lieve
Abstract: Background: End-of-life care in nursing homes holds several risk factors for the use of physical restraints on residents, a practice shown to be neither safe nor effective. Objectives: To determine the frequency of physical limb and/or trunk restraint use in the last week of life of nursing home residents in six European countries and its association with country, resident and nursing home characteristics. Design: Epidemiological survey study. Setting: Proportionally stratified random sample of nursing homes in Belgium (BE), England (ENG), Finland (FI), Italy (IT), the Netherlands (NL), and Poland (PL). Participants: Nursing home staff (nurses or care assistants). Methods: In all participating nursing homes, we identified all residents who died during the three months prior to measurements. The staff member most involved in each resident's care indicated in a structured questionnaire whether trunk and/or limb restraints were used on that resident during the last week of life 'daily', 'less frequently than daily' or 'not used'. Results: In 322 nursing homes, staff returned questionnaires regarding 1384 deceased residents (response rate 81%). Limb and/or trunk restraints were used "daily" in the last week of life in 8% (BE), 1% (ENG), 4% (FI), 12% (IT), 0% (NL), and 0.4% (PL) of residents; and "less frequently than daily" in 4% (BE), 0% (ENG), 0.4% (FI), 6% (IT), 0% (NL), and 3.5% (PL) of residents. Restraint use was associated with country ( p  = 0.020) and inversely associated with residents' age ( p  = 0.017; odds ratio 0.96, 95% confidence interval 0.93 to 0.99). Restraint use was not significantly associated with resident's gender, dementia, functional status, staffing level, or the level of dependency of residents within the nursing home. Conclusions: In all but one of the six countries studied, staff reported that nursing home residents were restrained through limb and/or trunk restraints in the last week of life. The proportion of restrained residents was highest in Italy and Belgium. Organizational and resident characteristics may not be relevant predictors of restraint use at the end of life in this setting. National policy that explicitly discourages physical restraints in nursing home care and suggests alternative practices may be an important component of strategies to prevent their use.